A randomized controlled trial of gaze‐contingent music reward therapy for major depressive disorder. Issue 2 (12th August 2020) - Shamai‐Leshem, Dana; Lazarov, Amit; Pine, Daniel S.; Bar‐Haim, Yair
Abstract: Background: Heightened attention allocation toward negative‐valanced information and reduced attention allocation toward positive‐valanced information represent viable targets for attention bias modification in major depressive disorder. Accordingly, we conducted a randomized controlled trial testing the efficacy of a novel gaze‐contingent attention bias modification procedure for major depressive disorder. Method: Sixty patients with major depressive disorder were randomly assigned to either eight training sessions of feedback‐based gaze‐contingent music reward therapy designed to divert patients' gaze toward positive over sad stimuli, or to a control condition which entailed eight sessions of gaze‐noncontingent music. Clinician‐rated and self‐reported measures of depression, and proportion of dwell‐time on sad faces, were assessed pretreatment, posttreatment, and at a 3‐month follow‐up. Results: Gaze‐contingent music reward therapy produced a greater reduction in dwell‐time on sad faces compared with the control condition, but it failed to generalize to novel faces. Both groups manifested similarly significant reductions in depression symptoms from pre‐ to posttreatment that were maintained at follow‐up. Exploratory analyses suggest that first‐episode patients may benefit more from this therapy than patients with a history of multiple episodes. Conclusions: Gaze‐contingent music reward therapy can modify attention biases in depression, but clear differential clinical effects did not emerge. Theoretical and practical implications are discussed.